The Effectiveness of the Results of the Security Council's Decision Regarding North Korea's Ceasefire Violations South Korea Sovereignty - Rully Agung Afrizal (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
This research focuses on examining the North Korean government's ambitions to expand its influence beyond the borders of other nations. Specifically, in this study, the President of South Korea responded quickly and efficiently to the protests lodged by him against the highest leader of the North Korean authorities, urging for an immediate meeting or dialogue regarding the recent violations of the armistice agreement by North Korea over the integral territory of South Korea, which is increasingly volatile at several strategic guard posts along the 248-kilometer border known as the Military Demarcation Line, cutting across the waist of the Korean Peninsula and following the Korean Demilitarized Zone that serves as the de facto border between the North and South.